Improvements in gait characteristics after intensive resistance and functional training in people with dementia: a randomised controlled trial - Schwenk, Michael; Zieschang, Tania; Englert, Stefan; Grewal, Gurtej; Najafi, Bijan; Hauer, Klaus (BMC geriatrics, 2014)
Preventing and rehabilitating gait disorders in people with dementia during early disease stage is of high importance for staying independent and ambulating safely. However, the evidence gathered in randomized controlled trials (RCTs) on the effectiveness of exercise training for improving spatio-temporal gait parameters in people with dementia is scarce. The aim of the present study was to determine whether a specific, standardized training regimen can improve gait characteristics in people with dementia.